Development of royal funerary traditions along the middle Nile valley during the Napatan Period (in the 7th century BC) - Balanda, Brigitte, (Studien zu den Ritualszenen Altagyptischer Tempel ; 31., 2020)
The Napatan Period is the link between Egypt and Meroe, in time, in space, and in culture. Stimuli from Egypt had been adopted to express and formulate indigenous ideas, which deve loped their own dynamics and eventually become recog nisable as the distinctive Meroitic culture. This thesis paves the way for a better understand ing of the inter-societal transfer of religious ideas and symbols, as well as their role in Nubian state formation.